2022
DOI: 10.1186/s42358-021-00232-1
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria and serum creatinine after 12 months of treatment for lupus nephritis as predictors of long-term renal outcome: a case–control study

Abstract: Background Lupus nephritis (LN) is a major source of morbidity and mortality in patients with systemic lupus erythematosus (SLE), with 10–25% of patients progressing to end-stage renal disease (ESRD). Objective This study aims to elucidate the predictive capabilities of 24-h proteinuria (24PTU) and serum creatinine (sCr) after 12 months of treatment with respect to long-term renal outcomes in LN in a single-center cohort of LN patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In agreement with this, a statistically signi cant correlation between serum creatinine and urinary protein was found in studies conducted on GN, nephrotic syndrome and CKD patients (47) (48) (49). Additionally, Braga et alshowed that serum creatinine and 24-hour urinary protein are surrogate markers for renal diseases in GN patients and both markers are associated with renal impairment (50). Another study reported absence of statistically signi cant correlation between proteinuria and serum creatinine among GN patients (51).…”
Section: Discussionmentioning
confidence: 57%
“…In agreement with this, a statistically signi cant correlation between serum creatinine and urinary protein was found in studies conducted on GN, nephrotic syndrome and CKD patients (47) (48) (49). Additionally, Braga et alshowed that serum creatinine and 24-hour urinary protein are surrogate markers for renal diseases in GN patients and both markers are associated with renal impairment (50). Another study reported absence of statistically signi cant correlation between proteinuria and serum creatinine among GN patients (51).…”
Section: Discussionmentioning
confidence: 57%